MANAJEMEN PESERTA DIDIK UPT SMP NEGERI 19 GRESIK - Muwafiqus Shobri; Firdaus Agustinu (Institut Agama Islam Darussalam Blokagung, 2023)
Student management can be a vehicle for raising school standards and performance. In order for students to succeed in an institution, there must be effective management of students with the aim of controlling students from the time they first enroll in school until they graduate. This study aims to determine the management of students which includes planning, coaching, evaluation, and transfer of students at UPT SMP Negeri 19 Gresik, and to find out the supporting and inhibiting factors in its implementation. This study used a phenomenon-oriented and qualitative approach, data collection was carried out by means of observation and interviews, documentation was then analyzed, and checked the validity of the data, was then presented. The results of this study are first that the management of students at UPT SMP Negeri 19 Gresik has been carried out optimally, and the two main supporting factors are the support of all educators and education staff and collaboration with student guardians, while the main obstacle is the limited facilities and the lack of funds for supervising extracurricular activities of participants educate.